(untitled) (Research, Society and Development, 2021)
Objective: to classify the prenatal care of women attended for childbirth in maternity hospitals in Espírito Santo, through a universal index, involving the recommendations of the World Health Organization (WHO), and a national index, from the Ministry of Health of Brazil (MHB), in addition to analyzing the factors associated with inadequate prenatal care. Methods: Cross-sectional study with postpartum women participating in the study “Born in Brazil” in maternity hospitals in Espírito Santo, between 2011-2012. Multivariate logistic regression was performed to verify the factors associated with inadequate prenatal care. Results: 450 postpartum women participated in the study. In more than half of the items that make up the WHO protocol, 80% or more was achieved. Iron and folic acid supplementation were the least performed items (20%). Based on the recommendations of the MHB, clinical-obstetric procedures were the most performed, while the uterine cervix cytopathological examination was the least recorded (9.3%). More than 50% of mothers had prenatal care considered inadequate. The factors associated with inadequate prenatal care were: not having a paid job (OR=2.09; 95%CI=1.22-3.57), not having an intention to become pregnant (OR=1.91 and OR=1.88; 95%CI=1.08-3.37), living outside the state capital (OR=1.87 and OR=1.91; 95%CI=1.11-3.17), prenatal care in the public sector (OR=4.92; 95%CI=1.65-14.68) and being multipara (OR=9.85; 95%CI=2.92-33.14). Conclusion: The most vulnerable women were the ones who had the most inadequate prenatal care, which requires changes in the way pregnant women are recruited and adhered to prenatal care, expanding the social role of public health services, based on predetermined prenatal protocols, in addition to expanding access to reproductive planning.